2013
DOI: 10.1309/ajcpdfbebqzw1oi7
|View full text |Cite
|
Sign up to set email alerts
|

CD177 Expression on Neutrophils

Abstract: Skewed low neutrophil CD177(%) is highly associated with clonal myeloid disorders, particularly myelodysplasia, and may be useful for detecting clonal myeloid disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…Our study population was made up of individuals of European, Asian and Australian self-reported ethnicity ( S2A Fig ). Consistent with previous reports [ 33 , 35 ], we identified three neutrophil populations according to CD177 expression: negative (neg), intermediate (int) and high (hi). The majority of individuals were bi-modal for CD177 (CD177 hi and CD177 neg ) ( Fig 1A ), while some individuals harbor a substantial proportion (>20%) of neutrophils expressing CD177 at intermediate levels ( Fig 1B ).…”
Section: Resultssupporting
confidence: 91%
“…Our study population was made up of individuals of European, Asian and Australian self-reported ethnicity ( S2A Fig ). Consistent with previous reports [ 33 , 35 ], we identified three neutrophil populations according to CD177 expression: negative (neg), intermediate (int) and high (hi). The majority of individuals were bi-modal for CD177 (CD177 hi and CD177 neg ) ( Fig 1A ), while some individuals harbor a substantial proportion (>20%) of neutrophils expressing CD177 at intermediate levels ( Fig 1B ).…”
Section: Resultssupporting
confidence: 91%
“…CD177 protein expression measured by FACS became evident on stages differentiated to metamyelocytes and further. These data corroborate the data of Stroncek et al, who investigated CD177 expression on fetal bone marrow samples [35] and also those of Meyerson et al, who showed that the most mature neutrophils, expressing CD16 and CD11b also had the highest CD177 expression [22]. Mora-Jensen et al used the same method for isolating neutrophil stages from the bone marrow and investigated the expression of proteins representing the different granules [25].…”
Section: Discussionsupporting
confidence: 84%
“…CD177 has been described to be a counter receptor for platelet endothelial cell adhesion molecule (CD31) on endothelial cells [19], but not for platelets [20]. Recently it was reported that there is no correlation between decreased apoptosis rate of neutrophils in AAV and the proportion of CD177 + cells [21], and others showed that low expression of neutrophil CD177 was highly associated with clonal myeloid disorders [22]. Because of the lack of knowledge on the biological function for CD177, we performed a gene microarray-based study to investigate differences between CD177 + and CD177 − neutrophils, in order to investigate whether there is a pathophysiologic background of an increased CD177 + /mPR3 high neutrophil subset for the pathogenesis of AAV.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting phenomenon that was not focus of our study is the occurrence of two CD177 pos peaks. Our observations are in agreement with the literature in that ∼5% of individuals show this CD177 pattern (Moritz et al, 2010;Meyerson et al, 2013;Wu et al, 2016). The molecular basis of this phenomenon is unclear and needs to be elucidated in future studies.…”
Section: Discussionsupporting
confidence: 92%